Outcomes of Pain Management Training for the Fourth- and Fifth-Year Medical Students - Ayano Saeki; Yumiko Takao; Keiichiro Suzuki; Munetaka Hirose (Pain Research and Management)
Pain management is a major medical issue. However, current medical education in Japan is inadequate with regard to training students to properly assess patients with acute and chronic pain and plan their treatment. Therefore, starting in 2019, Hyogo Medical University established a multidisciplinary educational system to better train medical students to provide pain care. The course, called clinical pain study, is offered to fourth- and fifth-year medical students. Fourth-year students learn the scientific aspects of pain through clinical practice. In this study, we assessed students’ understanding of pain management based on the results of pretests and posttests performed before and after their practicum. These tests were administered from November 2019 to April 2022 to 263 fourth- and fifth-year medical students who took the clinical pain study class. The test results were compared in terms of the percentage of correct answers and the total score for each question using McNemar’s chi-square test and paired t-tests, respectively. The results showed a significant improvement in the mean of the total score, confirming the improvement in medical students’ knowledge (6.43 vs. 7.35 points; p<0.001). Based on the results, overall, pain education at the university has had positive outcomes and will therefore be continued in the future.